2012
DOI: 10.4236/ojvm.2012.24035
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies Multistrain Probiotic Effects on Calves Development and Health

Abstract: Experiment was designed to assess alimentary security or any beneficial effect on calve of a multispecies multistrain probiotic (MMP). An experiment with 36 calves, two day old, was conducted to assess the influence of probiotic on growth and health indicators. The treatment period was extended to 45 d. Group 1 received one daily dose of MMP (1.1 × 10 9 CFU per calf) during 20 d. Group 2 was the untreated control. On a weekly basis, every calf in each group was weighed to determine weight gain. Forty five days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition, the time when calves are fed colostrum after birth might affect the effectiveness of DFM supplementation because colostrum has a profound effect on the functional development of the GIT. Passive immunity acquired through maternal immunoglobulins (IgG) in colostrum provides newborns with early protection against pathogens (Indart et al, 2012). Failure of passive transfer of immunity due to poor colostrum management leads to high incidence of diarrhea (Lorenz and Fagan, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the time when calves are fed colostrum after birth might affect the effectiveness of DFM supplementation because colostrum has a profound effect on the functional development of the GIT. Passive immunity acquired through maternal immunoglobulins (IgG) in colostrum provides newborns with early protection against pathogens (Indart et al, 2012). Failure of passive transfer of immunity due to poor colostrum management leads to high incidence of diarrhea (Lorenz and Fagan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Hurnik and Lewis (1991) suggested that the minimal space allowance requirement was 60% of the calf 's body surface area; this space allowance formula allows the calf to be able to stand and rest in sternal and lateral recumbency with its legs extended. Actually, the stressful conditions experienced by calves in commercial dairy operations can negatively influence the composition and symbiotic interactions of gut microbiota (Indart et al, 2012). Therefore, the administration of DFM to repopulate the gut might reduce the changes in the microbial population caused by stress (Krehbiel et al, 2003), and potentially improve performance and health in calves.…”
Section: Discussionmentioning
confidence: 99%
“…As consumer concern for the use of antibiotics in food animals increases, the development of alternative preventive and therapeutic strategies to enhance cattle health has become more relevant (Xiong et al, 2018). The administration of probiotics provides opportunities for managing the composition of the bacterial communities in the digestive tract and offers a novel approach for disease management (Indart et al, 2012;Hill et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In calves, the bacterial colonization of the gastrointestinal tract starts at birth. However, management practices in intense productive systems that expose young calves to stressful conditions might lead to microbiota disruption resulting in diarrhea (Indart et al, 2012;Cangiano et al, 2020). In consequence, supplementing newborn and young calves with probiotics might stimulate the growth of beneficial microorganisms, inhibiting the colonization by pathogens and enhancing calf health from birth to weaning (Gibson and Roberfroid, 1995;Hutkins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Certain multi-strain and multi-species probiotics have been reported to have immune- stimulating effects in cattle [ 6 , 14 , 15 ], and beneficial effects of probiotics have been recognized in improving animal health and protecting calves against infection [ 29 , 30 ]. Lactobacillus strains, alone or in combination with other probiotics, may reduce scouring in neonatal calves, increase weight gain and maintain health [ 13 , 14 ]. However, the interaction between probiotics and the function of host peripheral blood mononuclear cells (PBMCs) is not fully understood.…”
mentioning
confidence: 99%